A High-Capacity Ammonium Vanadate Cathode for Zinc-Ion Battery - Li, Qifei; Rui, Xianhong; Chen, Dong; Feng, Yuezhan; Xiao, Ni; Gan, Liyong; Zhang, Qi; Yu, Yan; Huang, Shaoming (Nano-Micro Letters, 2020)
Given the advantages of being abundant in resources, environmental benign and highly safe, rechargeable zinc-ion batteries (ZIBs) enter the global spotlight for their potential utilization in large-scale energy storage. Despite their preliminary success, zinc-ion storage that is able to deliver capacity > 400 mAh g−1 remains a great challenge. Here, we demonstrate the viability of NH4V4O10 (NVO) as high-capacity cathode that breaks through the bottleneck of ZIBs in limited capacity. The first-principles calculations reveal that layered NVO is a good host to provide fast Zn2+ ions diffusion channel along its [010] direction in the interlayer space. On the other hand, to further enhance Zn2+ ion intercalation kinetics and long-term cycling stability, a three-dimensional (3D) flower-like architecture that is self-assembled by NVO nanobelts (3D-NVO) is rationally designed and fabricated through a microwave-assisted hydrothermal method. As a result, such 3D-NVO cathode possesses high capacity (485 mAh g−1) and superior long-term cycling performance (3000 times) at 10 A g−1 ( 50 s to full discharge/charge). Additionally, based on the excellent 3D-NVO cathode, a quasi-solid-state ZIB with capacity of 378 mAh g−1 is developed. Highlights: 1 3D flower-like architecture assembled by NH4V4O10 nanobelts (3D-NVO) was fabricated. 2 The Zn2+ ion was intercalated into NVO cathode within the interlayer region (NH4V4O10 ↔ ZnxNH4V4O10). 3 The 3D-NVO cathode could deliver a large reversible capacity of 485 mAh g−1 at a current density of 100 mA g−1 for zinc-ion battery.